Widefield SERS for High‐Throughput Nanoparticle Screening. Issue 20 (16th March 2022) - Liebel, Matz; Calderon, Irene; Pazos‐Perez, Nicolas; van Hulst, Niek F.; Alvarez‐Puebla, Ramon A.
Abstract: Surface‐enhanced Raman scattering (SERS) imaging is a powerful technology with unprecedent potential for ultrasensitive chemical analysis. Point‐by‐point scanning and often excessively long spectral acquisition‐times hamper the broad exploitation of the full analytical potential of SERS. Here, we introduce large‐scale SERS particle screening (LSSPS), a multiplexed widefield screening approach to particle characterization, which is 500–1000 times faster than typical confocal Raman implementations. Beyond its higher throughput, LSSPS simultaneously quantifies both the sample's Raman and Rayleigh scattering to directly quantify the fraction of SERS‐active particles which allows for an unprecedented correlation of SERS activity with particle size. . Abstract : Large‐scale SERS particle screening is a multiplexed widefield screening approach for particle characterization. The method is 500–1000 times faster than typical confocal Raman implementations and simultaneously measures SERS and particle size.